Pembinaan Akhlak Mulia Berbasis Kitab Minhajul Abidin pada Remaja Akhir di Pondok Pesantren - Izar Alamul Huda; Ahmad Aly Syukron Al Mubarok (Kartika: Jurnal Studi Keislaman, 2026)
The lives of late adolescents in the modern era are confronted with various complex challenges, ranging from the influence of social media, free association, to identity crises that threaten the character and moral formation of the younger generation. Islamic boarding schools (pesantren) as Islamic educational institutions have a strategic role in fostering students' morals through the teaching of classical books, one of which is the Kitab Minhajul Abidin by Imam al-Ghazali. This study aims to describe the concept, implementation, and effectiveness of this book in addressing the life challenges of late adolescents at Pondok Panggung Lolawang Ngoro Mojokerto. The research employs a qualitative approach with a case study design, utilizing data collection techniques through in-depth interviews, observation, and documentation. The findings reveal that the concept of moral development is implemented gradually and systematically through life orientation toward Allah, identification of moral obstacles, self-control over desires, habituation of self-reflection (muhasabah), and the formation of steadfastness (istiqamah). The book is applied through bandongan (lecture-based) study sessions, contextualization of materials, habituation of worship, and continuous mentoring. The effectiveness of this moral development is evidenced by changes in students' behavior, including increased discipline in worship, emotional control, honesty, responsibility, as well as a shift in life orientation that views every activity as part of worship